1995
DOI: 10.1093/nar/23.22.4707
|View full text |Cite
|
Sign up to set email alerts
|

Consistences of individual DNA base—amino acid interactions in structures and sequences

Abstract: Amino acid-amino acid interaction energies have been derived from crystal structure data for a number of years. Here is reported the first derivation of normalized relative interaction from binding data for each of the four bases interacting with a specific amino acid, utilizing data from combinatorial multiplex DNA binding of zinc finger domains [Desjarlais, J. R. and Berg, J. M. (1994) Proc. Natl. Acad. Sci. USA, 91, 11099-11103]. The five strongest interactions are observed for lysine-guanine, lysine-thymin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 14 publications
(7 reference statements)
1
36
0
Order By: Relevance
“…*Values an average of at least two measurements. side chains, and T bases are more frequently contacted by Gln than Arg side chains (33).…”
Section: Resultsmentioning
confidence: 99%
“…*Values an average of at least two measurements. side chains, and T bases are more frequently contacted by Gln than Arg side chains (33).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the charged residues play a major role in the protein-nucleotide interactions [26][27][28]. We proceed to study the effect of this charge-charge interaction on translocation time.…”
Section: United Atom Modelmentioning
confidence: 99%
“…It seems reasonable to think that residues Arg-265 and Asn-268 mediate base-specific or nonspecific interactions with the DNA backbone, because arginine and asparagine are known to participate in such interactions (48). Since Leu-262 may comprise part of the ␣CTD hydrophobic core, the Leu to Ala substitution may lead to an altered conformation in which the presentation of residues directly contacting DNA and/or Mor is affected, resulting in reduced transcription activation.…”
Section: Fig 5 Interaction Trap Assaymentioning
confidence: 99%